Understanding Body Movement A Guide to Empirical Research on Nonverbal Behaviour - With an Introduction to the NEUROGES Coding System - Lausberg, Hedda (Peter Lang International Academic Publishers, 2013)
Understanding Body Movement is an interdisciplinary guide to empirical research on nonverbal behaviour. It focuses on tools and procedures to investigate body movement and gesture and the relation to cognitive, emotional, and interactive processes: NEUROGES, ELAN, interrater agreement, etc.